Influence of free silica in the production of synthetic aggregates from bauxite residue - M. B. de Vilhena; B. M. Viegas; J. A. S. Souza; E. N. Macêdo (Cerâmica, 2023)
Abstract The residue from the Bayer process has physicochemical characteristics that allow its use in the production of synthetic aggregate, although some characteristics such as low plasticity and water absorption still need better control. In this work, the influence of clay and silica addition on the sintering of synthetic aggregate produced from bauxite residue was analyzed. Compositions containing bauxite residue-sand-clay were elaborated, whose processing occurred using extrusion and crushing, followed by sintering at 1200 °C for 3 h. The X-ray diffraction analyses indicated the presence of new phases such as nepheline, originating from sodalite, and mullite resulting from the decomposition of kaolinite. Increasing the amount of free silica in the mixture resulted in an aggregate with a higher bulk density and lower water absorption, indicating that the amount of this raw material influenced the aggregate properties.